Highly efficient removal of patulin using magnetic Fe3O4 nanoparticle-immobilized Papiliotrema flavescens - Mengyang Xing; Qiu Long; Yong Chen; Shiping Tian; Boqiang Li (Food Chemistry, 2026)

Changes in soil properties and C, N, and P functional microbial communities in three cropping systems under interactions between soil type and moisture management - Shaojun Qiu; Qiusheng Wu; Siwen Peng; Yulin Liao; Quan Yuan; Xiubin Wang; Shiping Long; Peter Christie (Applied Soil Ecology, 2026)

Achieving “one stone, three birds”: A solid-waste steel-slag-derived system for synergistic antibiotic degradation and CO2 capture - Shiping Zhang; Xiaoyong Wu; Baolin Zhao; Gui Yang; Shenxu Bao; Xueying Chen; Ling Xia; Yao Wang; Juan Long; Yang Wu; Lin Wang; Binbin He (Journal of Cleaner Production, 2026)

Anti-interference monitoring system of nitrogen dioxide and ammonia gas via metal (Cu, Ni, and Pd) doped-CeO2 sensing array combining with CPO-BPNN model in intelligent agriculture - Detao Lu; Haoming Zhang; Long Huang; Shiping Zhu; Wen Zeng; Qu Zhou (Chemical Engineering Journal, 2025)

Tobacco black shank disease significantly affects the composition and assembly of the genotype-associated microbial community in the rhizosphere - Qipeng Jiang; Jiamin Yu; Min Mao; Lianqiang Jiang; Fangfang Yan; Ruiyu Yang; Minfeng Yang; Chengzhi Weng; Shiping Guo; Dongyang Liu; Xiangwen Yu; Quan Deng; et al. (Applied Soil Ecology, 2025)

Unlocking the potential of supramolecular polymers with bimodal molecular weights for instant and strong underwater adhesion - Wenlian Qiu; Yi Huang; He Zhu; Yi Long; Qi Zhang; Shiping Zhu (Chemical Engineering Journal, 2024)

Ptercresions A-C: three new terpenes with hepatoprotective activity from Pteris cretica L - Jianping Hu; Shiping Liu; Ying Long; Ning Tao; Bo Yang; Liyong Zhang (Natural Product Research, 2022)

Electrochemical crystallization for recovery of phosphorus and potassium from urine as K-struvite with a sacrificial magnesium anode - Jinhua Shan; Hongbo Liu; Shiping Long; Haodong Zhang; Eric Lichtfouse (Environmental Chemistry Letters, 2022)

Dissection of patulin biosynthesis, spatial control and regulation mechanism in Penicillium expansum - Boqiang Li; Yong Chen; Yuanyuan Zong; Yanjiao Shang; Zhanquan Zhang; Xiaodi Xu; Xiao Wang; Manyuan Long; Shiping Tian (Environmental Microbiology, 2019)
Summary The patulin biosynthesis is one of model pathways in an understanding of secondary metabolite biology and network novelties in fungi. However, molecular regulation mechanism of patulin biosynthesis and contribution of each gene related to the different catalytic enzymes in the biochemical steps of the pathway remain largely unknown in fungi. In this study, the genetic components of patulin biosynthetic pathway were systematically dissected in Penicillium expansum , which is an important fungal pathogen and patulin producer in harvested fruits and vegetables. Our results revealed that all the 15 genes in the cluster are involved in patulin biosynthesis. Proteins encoded by those genes are compartmentalized in various subcellular locations, including cytosol, nucleus, vacuole, endoplasmic reticulum, plasma membrane and cell wall. The subcellular localizations of some proteins, such as PatE and PatH, are required for the patulin production. Further, the functions of eight enzymes in the 10‐step patulin biosynthetic pathway were verified in P. expansum . Moreover, velvet family proteins, VeA, VelB and VelC, were proved to be involved in the regulation of patulin biosynthesis, but not VosA. These findings provide a thorough understanding of the biosynthesis pathway, spatial control and regulation mechanism of patulin in fungi.